Thymoquinone loaded nanostructured lipid carriers (TQ-NLC) and uses thereof - Saiful Yazan, Latifah; Ng, Wei Keat; Abdullah, Rasedee; How, Chee Wun (2012)

(untitled)
The present invention relates to the synthesis of thymoquinone loaded nanostructured lipid carrier (TQ-NLC) having water soluble properties.